2017
DOI: 10.1016/j.bbamem.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

High resolution mass spectrometry characterization of the oxidation pattern of methionine and cysteine residues in rat liver mitochondria voltage-dependent anion selective channel 3 (VDAC3)

Abstract: Voltage-dependent anion selective channels (VDACs) are integral membrane proteins found in the mitochondrial outer membrane. In comparison with the most abundant isoform VDAC1, there is little knowledge about the functional role of VDAC3. Unlikely VDAC1, cysteine residues are particularly abundant in VDAC3. Since the mitochondrial intermembrane space (IMS) has an oxidative potential we questioned whether the redox state of VDAC3 can be modified. By means of SDS-PAGE separation, tryptic and chymotryptic proteol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Cysteines respond to mitochondrial oxidative stress through oxidative modifications of their side chain (Guardiani et al, 2016; Reina et al, 2016a,b; Saletti et al, 2017, 2018; Sorrentino et al, 2017; Iadanza et al, 2018). In particular, hV3 is known to oligomerize and aggregate upon oxidation of its cysteines to S–OH, S–O 2 H, and S–O 3 H (Okazaki et al, 2015; De Pinto et al, 2016; Guardiani et al, 2016; Reina et al, 2016a,b; Saletti et al, 2017). Our recent reports (Reina et al, 2016a) also identify the susceptibility of hVDAC3 to aggregation under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cysteines respond to mitochondrial oxidative stress through oxidative modifications of their side chain (Guardiani et al, 2016; Reina et al, 2016a,b; Saletti et al, 2017, 2018; Sorrentino et al, 2017; Iadanza et al, 2018). In particular, hV3 is known to oligomerize and aggregate upon oxidation of its cysteines to S–OH, S–O 2 H, and S–O 3 H (Okazaki et al, 2015; De Pinto et al, 2016; Guardiani et al, 2016; Reina et al, 2016a,b; Saletti et al, 2017). Our recent reports (Reina et al, 2016a) also identify the susceptibility of hVDAC3 to aggregation under oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…The other cysteines (C36 and C122) are present in large hydrophobic segments. It has not been possible to map these peptides even in prior MS studies of hV3, owing to the extremely hydrophobic nature and poor ionization efficiency of these segments (Saletti et al, 2017). MS fingerprinting using other proteases such as pepsin also did not yield the peptide fragments corresponding to these cysteines (not depicted).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the oxidation state of cysteines was found to be important for the insertion and activity of VDAC3 samples (Reina et al, 2016b). It must be pointed out that in these previous works, any reducing agent was avoided during purification and reconstitution steps, with the purpose of not altering the naturally occurring oxidation state of cysteines (Reina et al, 2016a; Saletti et al, 2017). In the present study, all VDAC3 samples tested showed transitions between an open state to a variety of closed states, with very similar gating characteristics to VDAC1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The substrate chosen for the photocatalytic oxidation investigation was the amino acid, l -methionine [ 40 ]. Its selective oxidation to the sulfoxide represents a model for the oxidation of methionine residues in proteins (see for example: 41 44 ]). An aqueous solution of l -methionine containing 0.06 mol% of TPyCP was irradiated with red light ( λ exc = 660 nm) and the reaction mixture was monitored by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%